Chaperones for intimate examinations in family medicine: findings from a pilot study in Melbourne, Australia. (January 2015) - Jones, Kay; Biezen, Ruby; Beovich, Bronwyn; van Hecke, Oliver
Background: The use of medical chaperones during clinical examinations is important whether one practises as a specialist, nurse, medical student or generalist. Chaperone use in general practice remains largely unknown in most countries across the world and, what is known is limited to a handful of countries. Their use in Australian general practice remains unknown. Objective: To explore the attitudes and practices of a cohort of general practitioners in urban Melbourne regarding the use of chaperones in their daily clinical practice. Methods: Self-administered postal questionnaire to pilot group of general practitioners in urban Melbourne, Australia. Main outcome measures: Frequency of chaperone use; views on chaperone use itself; preferred choice for the role of chaperone; main reasons for using chaperones. Results: The majority (95% respondents) had never or occasionally used a chaperone. The use of chaperones correlated with general practitioner gender – male general practitioners were more likely to use a chaperone. General practitioners preferred choice as chaperone was the practice nurse. There was no association found between chaperone use and the respondents' age, practice size or the availability of a practice nurse. The most highly rated influence by general practitioners for using a chaperone was because of anticipated patient embarrassment and/or distress. Conclusion: This is the first step in understanding attitudes and experiences of general practitioners in general practice in Australia. The results of a larger, national study would provide further insight into this important issue taking into account the realities of general practice in Australia and relationship between general practitioners and patients.